2021
DOI: 10.21831/pg.v16i1.35729
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical model of cholera spread based on SIR: Optimal control

Abstract: The bacterium Vibrio cholerae is the cause of cholera. Cholera is spread through the feces of an infected individual in a population. From a mathematical point of view, this problem can be brought into a mathematical model in the form of Susceptible-Infected-Recovered (SIR), which considers the birth rate. Because outbreaks that occur easily spread if not treated immediately, it is necessary to control the susceptible individual population by vaccination. The vaccine used is Oral Vibrio cholera. For this reaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Mathematical modeling has been extensively used in many different fields of study including medicine, physics, economics, and so on [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Medical research issues, especially high-level medical research achievements, often rely on the establishment of reasonable medical mathematical models [7][8][9][10][11][12][13][14][15][16][17][18][19][20]. For example, Tripathi et al [7] provided several examples of designing various mathematical models that can help us better comprehend dynamics at the single-cell and population levels.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Mathematical modeling has been extensively used in many different fields of study including medicine, physics, economics, and so on [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Medical research issues, especially high-level medical research achievements, often rely on the establishment of reasonable medical mathematical models [7][8][9][10][11][12][13][14][15][16][17][18][19][20]. For example, Tripathi et al [7] provided several examples of designing various mathematical models that can help us better comprehend dynamics at the single-cell and population levels.…”
Section: Introductionmentioning
confidence: 99%
“…The established model with the use of new epidemiological data can provide theoretical support for the prevention and control of infectious diseases, expose the mechanism of transmission, and facilitate the development of national and even international health policies [10]. After the outbreak of infectious diseases such as Ebola, COVID-19, and Plague, several domestic and foreign scholars refined the existing infectious disease models in use to analyze their epidemiological characteristics [11][12][13][14][15][16][17][18][19][20]. For example, a study [11] used two modified susceptible-infected-removed (SIR) models to simulate the transmission dynamics of Ebola, and the results showed that although there are currently no specific drugs to treat Ebola, effective isolation measures can better manage and control its transmission.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, in 2019 another research was carried out by Hasanah regarding optimal control of preventing the spread of cholera by controlling treatment and chlorination [10]. Research on the spread of cholera using the SIR model was also carried out by Hidayati, et al (2021) with vaccination control [11].…”
Section: Introductionmentioning
confidence: 99%